Evaluation of maize (Zea mays) based intercropping for productivity, resource-use efficiency and competition indices in the rainfed foothills of northwest Himalayas - SINGH, SHER; BAWA, S S; SINGH, SATVINDER; SHARMA, S C (The Indian Journal of Agricultural Sciences, 2015)
A three-year (2009-2011) field experiment was conducted to study competitive behaviour of maize (Zea mays L.)+ legume/oilseed based additive series paired-row intercropping at the Punjab Agricultural University's Regional Research Station for Kandi Area, Ballowal Saunkhri. The experiment comprised 10 treatments viz. 4 sole plantings of maize, blackgram [Vigna mungo (L.) Wilczek], greengram (Vigna radiata L.) and sesame (Sesamum indicum L.) each, and six intercropping treatments. Among two planting patterns, 100 maize:33 intercrop mix proportion proved superior for maize yield than 100:67 for all the intercrops. The productivity (3.07 tonnes/ha) and sustainability yield index (0.69) were highest when 1 row of greengram was intercropped with maize (2 M:1 G). Inclusion of legumes in intercropping improved both production and rain water use efficiencies with definite yield and economic advantage. The higher land equivalent ratio (1.27) and relative crowing coefficient (20.4) values for 2 M:1 G planting pattern indicated more efficient benefits and maximum maize yield advantage. As per values of aggressivity, greengram (2 rows) proved most competitive (Â±0.0005) while sesame (2 rows) least competitive (±0.0046) to maize. Among intercrops, the competitive ratio was highest (1.42) for greengram followed by blackgram in both the planting patterns. 2 M:1 G provided 9.8% (actual yield loss=+0.098) yield gain as compared to sole cropping. In the maize+greengram planting patterns, area time equivalent ratio values indicated yield advantages in the range of 19% for 2 M: 1G and 17% for 2 M:2 G. Thus, inclusion of legumes (especially greengram) in maize culture system can achieve a sustainable and economic yield advantage along with shorter system duration compared to their monocultures.